Ligustrum Weevil (suggested common name), Ochyromera ligustri Warner (Insecta: Coleoptera: Curculionidae: Tychiinae: Tychiini: Endaeina) - James P. Cuda; M. C. Zellar; Michael C. Thomas (EDIS, 2005)
A seed-attacking weevil was recently found attacking Chinese privet in Tallahassee, Leon County, Florida (Cuda and Zeller 1998). The insect was discovered in a sample of several hundred seeds collected for germination studies. Six weevil adults that emerged from the infested seed sample were later identified (by M.C. Thomas) as the ligustrum weevil, Ochyromera ligustri Warner. The remaining seed stock from Tallahassee was dissected and inspected for the presence of the insect. Weevil larvae were recovered from 89 of the 358 seeds examined. Overall, 24.9% of the Chinese privet seeds collected were infested with weevil larvae. Voucher specimens of the larval and adult stages of the ligustrum weevil were deposited in the Florida State Collection of Arthropods, Division of Plant Industry, Florida Department of Agriculture and Consumer Services, Gainesville. This document is EENY-343, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2005.